2022
DOI: 10.3390/sym14030469
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Measuring the Cutting Inserts Wear

Abstract: In the industrial manufacturing, the wear of the cutting tool represents the main factor that causes machine downtime and it has a negative influence over the machined surface roughness and dimensional and position deviations. For this reason, the accurate measurement of tool wear both on-line (during machining) and off-line (outside of the machining process) is a necessity. Due to the continuous technology innovation, finding new and more effective methods to measure precisely the wear represents a permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…In the automotive industry, there are tribological pairs, such as coating-substrate or coating-coating (in the case of multi-layer coatings), which exhibit high wear resistance despite their small thickness (a few micrometers). Studies show that with an increase in the thickness of the coatings, even a small amount of wear can become more intense [1][2][3]. This confirms that tribological methods should be used to evaluate the tribological characteristics of coatings, and not any other approaches.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the automotive industry, there are tribological pairs, such as coating-substrate or coating-coating (in the case of multi-layer coatings), which exhibit high wear resistance despite their small thickness (a few micrometers). Studies show that with an increase in the thickness of the coatings, even a small amount of wear can become more intense [1][2][3]. This confirms that tribological methods should be used to evaluate the tribological characteristics of coatings, and not any other approaches.…”
Section: Introductionmentioning
confidence: 73%
“…Understanding the characteristics of each material used in complex multilayer or composite coatings, predicting the behavior of such a composite becomes a challenge, as it depends on many factors: chemical composition, proportions of components, application technology and thickness of the coating itself. The interaction of heterogeneous elements leads to an effect equivalent to the creation of a new material [1], the properties of which differ from the properties of each individual component in terms of qualitative and quantitative indicators. The difference in the characteristics of materials is directly related to their composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the cutting tool, notably determines the outcome of the nished product. However, a notable area of concern is the issue of the tool wear, which according to Daicu and Oancea [2] are mostly traceable to certain parameters ranging from the choice of cutting tool material, hardness of workpiece material, geometry of the cutting tool, cutting uid, and the selected metal cutting parameters. All these signi cantly dictate, and contribute to the overall manufacturing cost of the nished products [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey conducted across multiple manufacturing facilities, it was found that manual tool wear observation accounts for approximately 30% of unscheduled machine downtime due to incorrect assessments and the time needed for inspections. Moreover, the subjectivity of these methods introduces variability in tool wear assessment across different operators, making it challenging to establish consistent maintenance schedules [2,3].…”
Section: Introductionmentioning
confidence: 99%